Experimental derivation of stiffness matrix of sheet metal joint - Yusoff, Abdul Hafiez (2013)
The thesis presents the study on the three-dimensional experimental derivation stiffness matrix of sheet metal joint substructure based on the basic principle of finite element method (FEM). Normally in FEM, the material properties of a complete structural system can be represented by Young‟s modulus, Poisson‟s ratio, density, surface area and etc but if the structure deflection influence coefficients or stiffness matrix are known, the behavior of complete structural system can be defined. One of user defined element existed in NASTRAN that rarely used is general (GENEL) element, the GENEL entry is used to define general elements whose material properties are defined in terms of deflection influence coefficients or stiffness matrix which can be connected between any number of grid points. A systematic approach of stiffness matrix extraction of a sheet metal joint has been successfully studied and developed. The experimental stiffness matrix which represents the actual behavior of the substructure is then entered into NASTRAN as a new element, GENEL. Comparison of results between the experimental and the finite element analysis is carried to validate the method employed. Excellent agreement with the experimental results has been observed which confirms the accuracy of the approached employed. The methodology of extraction stiffness coefficients experimentally has also been successfully developed on the basis of the direct stiffness method.